1988
DOI: 10.1111/j.1398-9995.1988.tb02040.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose local steroid treatment in bronchopulmonary aspergillosis

Abstract: Two patients with allergic bronchopulmonary aspergillosis (ABPA) have been treated with a high dose (1600 micrograms daily) of inhaled corticosteroid for 18 months. A beneficial effect with regard to asthmatic symptoms was observed in both patients. During the first 14 months of the observation period no significant changes were observed in lung function parameters. Bronchial histamine challenge showed decreased hyperreactivity. IgE decreased in both patients, while specific IgE and IgG remained the same. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…However, this study used low doses of ICS (400 μg beclomethasone per day) and spacers were not employed. Small case studies have suggested variable benefits of ICS in the management of ABPA (17)(18)(19)(20). Thus, the exact role of ICS in ABPA is poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study used low doses of ICS (400 μg beclomethasone per day) and spacers were not employed. Small case studies have suggested variable benefits of ICS in the management of ABPA (17)(18)(19)(20). Thus, the exact role of ICS in ABPA is poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled corticosteroids, while useful for concomitant asthma management in patients with ABPA, do not control the pathophysiology or clinical manifestations of ABPA [116][117][118][119][120]. In contrast, ''pulse'' steroid therapy (10-20 mg?kg -1 ?day -1 i.v.…”
Section: Alternative Corticosteroid Regimesmentioning
confidence: 99%
“…Prednisone remains the mainstay of therapy for ABPA [8,9]. High dose of inhaled steroids may be useful in some patients and may allow reduction in the dose of oral corticosteroids [14].…”
Section: Discussionmentioning
confidence: 99%